Testing the ice : a true story about Jackie Robinson - Robinson, Sharon, 1950- (Scholastic Press, 2009)
As a testament to his courage, Jackie Robinson's daughter shares memories of him, from his baseball career to the day he tests the ice for her, her brothers, and their friends.